Translating Cultural-Historical Psychology: Comments from Lay Professional (Revue internationale du CRIRES : innover dans la tradition de Vygotsky, 2017)
In translating texts for the Chess Overall Development Project (Zaretskii, 2016), we have encountered several types of challenges that may be illustrative of what translators in the ﬁeld of cultural-historical psychology (CHP) may deal with. Translators use various tools and strategies in their search for equivalence. Lack of the uniform CHP vocabulary and consensus on the CHP terms: di˙erences in transformational techniques and levels of the translators’ linguistic competence and their competence in CHP as such, result in co-existence of various translations of the same concepts, which may interfere with the process of communication and become a subject of controversy. Other challenges relate to speciﬁc linguistic features of the psychological scientiﬁc discourse of CHP, i.e. the need to observe rigorous scientiﬁc requirements to style and content, and abundance in expressive, emotionally and culturally charged utterances and vocabulary. The CHP terminology is characterized by speciﬁc word formation; lack of stylistic neutrality and lack of equivalent terms in target languages. Therefore, an appropriate translation implies using a special modiﬁcation technology to create a target-language term which would have an equivalent denotative meaning; meet the requirements of the scientiﬁc style and preserve its stylistic uniqueness, emotional, and cognitive relevance (ensuring congruence of the reader’s experience with the author’s experience as mirrored by the lexical unit).
Keywords: Cultural-historical psychology; Translation; Psychological discourse; Terminology; Connotation; Scientific style